Requirements of Employers for Young Specialists and Issues of Their Training at the Educational Institutions: Regional Specificity of Moscow - Bobkov, Vyacheslav Nikolaevich; Litvinyuk, Alexander Aleksandrovich; Ledneva, Svetlana Anatolyevna (Economy of Regions, 2016)
The subject-matter of the article is the study of the peculiarities of the youth labour market in such a specific region of Russia as the city of Moscow. The topic of the work is connected to the adaptation of young specialists training system to the regional requirements of the employers of Moscow. The main hypothesis of the research assumes that Moscow is the atypical region of Russia and it is inexpedient to apply criteria and methodological approaches, which are standard for our country, to its labour market. As a method of the research, a selective survey of key employers of Moscow and respondents aged from 14 till 30 years has been used. The data of the sociological survey conducted by the authors have allowed to establish the following features of the researched region: a respectively low level of youth unemployment compared with the whole Russia; focusing of employers on such features of personnel as a good communicative skills learning ability, professional knowledge and competences. Moscow employers don’t pay significant attention to such characteristics of young specialists as language and computer skills, computer knowledge and the diploma of a prestigious educational institution. The main difficulties in finding employment for young specialists in the city of Moscow are: overestimated salary expectations; the weak professional training level and unwillingness, in fact, to work. As a result of the survey, the practical offers have been formulated. There are two directions of their application: the offers focused on the behaviour of the youth at a stage of their training and those offers focused on the increase of a practical component of the activity of professional educational institutions. The authors came to conclusions about the need of a deep orientation of educational institutions to the applied training for specialists, of practical workers for teaching special disciplines, the development by future specialists their abilities to present themselves and the results of their work to the professional environment (self-presentation skills) and to objectively estimate real opportunities of their employment.